Social web and information literacy: experience of the University of Puerto Rico - Pagán, Liz M. (2016)
This research explores and describes the adoption of the social web for information literacy by the libraries of the University of Puerto Rico (UPR). The objectives of this study are to: identify the social web technologies used by librarians for information literacy; identify the technologies and the extent of use; evaluate the librarian’s attitudes towards the application of the social web; identify the technology connection with the Association of College and Research Libraries (ACRL) standards. The methodological approach of the study is qualitative, and the data collection techniques are the questionnaire and the interview. The results show that 82% of the participants of this study use the social web for information literacy. The preferred technologies by librarians are: blogs, social networks, media sharing, and mashup. While the technologies most frequently use are: media sharing (Flickr, YouTube, Instagram, and Pinterest), blog and social networks. The participants presented an attitude of acceptance towards the application of the social web for information literacy and they expressed the connection between the ACRL standards and the use of the social web through teaching. Based on the results of this study, recommendations are presented regarding the current application of social web tools for information literacy.